THE IMPLEMENTATION OF A THEORY-BASED PRACTICE METHOD IN TEACHING ENGLISH MATERIALS DEVELOPMENT (EMD) COURSE FOR STUDENTS OF ENGLISH PROGRAM OF IAIN TULUNGAGUNG - Iftanti, Erna (Jurnal Bahasa Lingua Scientia, 2014)
An English teacher should be able to develop English instructional materials which are more culturally appropriate to his students? cultural context. This is important to help them learn English in their own areas in terms of either the context or the content of instruction which then bring about producing the joy of learning English. Therefore, this paper discusses about my journey of implementing a theory-based practice method to teach students of teacher training education of English Program of IAIN Tulungagung in developing English Instructional Materials. In implementing this method I explained some theories related to developing English instructional materials and the students were guided to do need analysis and to practice developing the materials of English instruction. With this method the students focus on practicing English materials development based on the theories taught. The results of this research indicate that the students have rich learning experiences in developing instructional English materials in accordance to their own selected level of education compared to using fully theory based method to teach English Material Development (EMD).